Evaluation of Antibacterial Properties from Endophytic Fungi of Chrysanthemum indicum (L.) Flowers against Escherichia coli and Staphylococcus aureus - Ratte, Titah Amelia; Fatimawali, Fatimawali; Tallei, Trina Ekawati; Suoth, Elly Juliana; Antasionasti, Irma; Yamlean, Paulina (Graha Primera Saintifika, 2023)
Uncovering the therapeutic potential of secondary metabolites produced by plants, animals, and microbes constitutes the foundation for the development of novel medications. The objective of this investigation is to discern the classes of secondary metabolites and assess the antibacterial properties of endophytic fungal extracts obtained from Chrysanthemum indicum L. flowers. Through the isolation process, five isolates designated as JEC1, JEC2, JEC3, JEC4, and JEC5 were identified. The cultivation of endophytic fungal isolates spanned a three-week period before undergoing extraction with ethyl acetate. The phytochemical tests revealed the presence of alkaloids, flavonoids, steroids, terpenoids, saponins, and tannins in the ethyl acetate extract. Antibacterial activity was determined using the agar well diffusion method, with ciprofloxacin serving as a positive control. Notably, all ethyl acetate extracts from endophytic fungi exhibited antibacterial activity. The most substantial inhibitory diameter against Staphylococcus aureus was recorded as 19.1±0.8 mm for the JEC3 endophytic fungi, while Escherichia coli exhibited an inhibitory diameter of 16±1.1 mm for the JEC2 endophytic fungi.